A new species-complex within the trapdoor spider genus Nemesia Audouin 1826 distributed in northern and central Italy, with descriptions of three new species (Araneae, Mygalomorphae, Nemesiidae) - Decae, Arthur; Pantini, Paolo; Isaia, Marco (Zootaxa, 2015)
Three new Nemesia Audouin 1826 species from northern and central Italy are named. They share a combination of sexual characters, not found in other described species. A new species-complex within Nemesia is here referred to as the apenninica group. Within the apenninica group, N. apenninica n. sp., N. hastensis n. sp., and N. pedemontana n. sp. differ in the morphology of the male palpal organ and the female spermathecae. The three species have different kinds of geographical distributions. While N. apenninica and N. hastensis have locally restricted and geographically separated distributions, the distribution of N. pedemontana overlaps with that of both of these species and extends widely in northern and central Italy. In its periphery, the distribution of N. pedemontana overlaps with that of species other than the apenninica group, e.g., N. meridionalis (Costa, 1835) in southern Italy and N. manderstjernae (L. Koch, 1871) and N. carminans (Latreille, 1818) in Liguria. Information on burrow structure, phenology and habitat are provided for all three new species. Some aspects of the behavior and feeding are discussed for N. pedemontana and N. hastensis.